PENGARUH KEPEMILKAN INSTITUSIONAL DAN KEPEMILIKAN KELUARGA, TERHADAP KINERJA PERUSAHAAN PUBLIK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015 - Putri, Bestari Adji (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims at analyzing the effect of institutional ownership and family ownership on the performance of public companies listed on Indonesia Stock Exchange in 2018. The purposive sampling method is applied in this study. The kind of data in this study is the secondary data which is the financial report of the companies in 2018. Based on the criteria, there are 70 companies used as samples for this study. Then the data are analyzed by utilizing the multiple linear regression method. The result shows that institutional ownership has a positive or simultaneously significant effect on the companies’ performance. The equal result is also shown that the family ownership has a positive or significant influence on the company’s performance.Key words: institutional ownership, family ownership, and company’s performance